Growth, Yield and Profitability of Summer Country Bean (Lablab Purpureus L.) As Influenced by Exogenous Application of Plant Growth Regulators (Bangladesh Journal of Agricultural Research, 2023)
A field experiment on summer country been (var. BARI Shim-7) was conducted at the Research Field of Plant Physiology Section of Horticulture Research Center, Bangladesh Agricultural Research Institute (BARI), Gazipur, during the summer season of 2018 and 2019 to study the effect of exogenously applied plant growth regulators (PGRs) on growth, yield and profitability of the crop. The experiment was consisted of four levels of NAA (15, 30, 45 and 60 ppm), three of CCC (200, 300 and 400 ppm), two of GA3 (20 and 30 ppm) and tap water as control. Average results of two years showed that all growth regulators performed better in respect of all characters studied over control. At 1st fruit set vine length (3.15 m) and number of leaves/plant (327.96), at last harvest stem girth (24.53 mm) and vine length (4.89 m), and plant dry matter (17.24%), number of pods/cluster (6.41), pod length (8.78 cm), number of pods/plant (351.30), individual pod weight (6.26 g) and pod set (38.13%) were the maximum in 60 ppm NAA followed by 45 ppm NAA and 200 ppm CCC. The maximum mean pod yield (10.65 t/ha) was obtained with the application of 60 ppm NAA closely followed by 45 ppm NAA (10.50 t/ha). Application of 200 ppm CCC also produced higher pod yield (8.75 t/ha) than that of control. Application of 60 ppm NAA also gave the maximum gross return (Tk. 532500/ha), gross margin (Tk. 3361248/ha) and BCR (3.11).Bangladesh J. Agril. Res. 47(1): 13-22, March 2022